Improved Learning of the Healthy Living Community Movement During the Pandemic for Budi Cendekia Islamic School Students - Erlina Puspitaloka Mahadewi; Mohamad Reza Hilmy; Intan Silviana Mustikawati; Suryari Purnama; Arman Harahap (International Journal Of Community Service, 2021)
Changes in disease patterns in Indonesia are often referred to as the epidemiological transition. In the 1990s the biggest cause of death and illness was infectious diseases. However, in the era of the last 10 years from 2010 to 2020 the biggest causes and causes of death and illness are non-communicable diseases. The increased risk of non-communicable diseases is due to the demographic transition. The Healthy Living Community Movement or commonly known as GERMAS is a movement initiated by the President of the Republic of Indonesia that prioritizes promotive and preventive efforts without compromising curative-rehabilitative efforts. This activity aims to raise public awareness, especially high school students, to be independent in doing GERMAS. Especially in disseminating information about the importance of implementing GERMAS during the Covid-19 pandemic. The activity is carried out using the seminar method, and was carried out by a team of 10 students, 1 lecturer and 1 health practitioner. The implementation time during this community service takes place which is 15 to 20 minutes for each topic with a presentation. After carrying out a series of activities, the committee provides an evaluation link that can be filled in by the participants. The results of the research show that the success rate is above 51% and shows that this community service will affect the target in carrying out GERMAS even though this activity is carried out virtually using the zoom meeting application. The activity in the next future needs to be improved again in the delivery of material and in answering the material in a language that is easily understood by high school students.